The impact of BRICS formation on portfolio diversification: Empirical evidence from pre- and post-formation eras - Somar Al-Mohamad; Audil Rashid; Walid Bakry; Ammar Jreisat; Xuan Vinh Vo (Cogent Economics & Finance, 2020)
This paper aims at contributing to the international portfolio investment decisions among the emerging BRICS countries where individual and institutional investors seek diversification benefits and to help in advocating policy changes and implementation as a response to the changing dynamics in these countries pre- and post-BRICS formation. Therefore, the context of this paper is aimed towards examining the short term causalities and long term integration among the BRICS stock market pre- and post-BRICS formation. The research applies the Augmented Dicker-Fuller (ADF) and Philips-Perron tests (PP) tests to analyze stationarity among the selected variables. The pre- and post-BRICS formation long-term linear relationship is investigated using Johansen and Juselius cointegration test while the Granger Causality is applied to assess the direction of the causality between the stock market indices. The study also extends the investigation by employing the impulse response function and variance decomposition to evaluate the reaction of each of the BRICS market to a shock from other BRICS stock markets. Weekly stock market indices of BRICS countries were used covering the period from January 2003 to December 2018. One key finding is that the degree of financial integration among the BRICS stock markets has moderately strengthened in the post-BRICS formation period compared to the pre-BRICS formation period. Another significant finding is that the Chinese stock market are mostly independent from other BRICS markets in the two aforementioned sub-periods, implying diversification benefits for the international investors both in the short and the long run. Further, the results also reveal a unidirectional causal relationship from the Russian stock market to its BRICS counterparts in both periods. Finally, the overall results show an increased responsiveness of stock markets in BRICS countries to shocks in each other after the formation of the bloc as compared to pre- formation period.
Keywords: C58; F36; G11; G15; 330; BRICS; financial integration; Johansen-Juselius cointegration test; Granger causality; portfolio diversification; impulse response function; variance decomposition analysis